The Influential Factors of Student Understanding in Mathematics Lessons - Fauzi, Miftah; Wulanda, Mastarita Nova; Qamaruddin, Qamaruddin (IJER (Indonesian Journal of Educational Research), 2023)
The purpose of this study was to determine the factors that influence the understanding of student in mathematics lesson at elementary school in Jambi. The research approach is descriptive qualitative. Data collection techniques were carried out by interviews to teachers and students at Sekolah SD Islam Al Azhar 57 Jambi. The study was carried out from January to February 2023. The results showed that the dominant influencing factors of elementary school students in understanding mathematics lesson could be categorized as internal and external factors. The internal factors were students’ interest, motivation, attitude and effort to grasp the lesson, while the external ones namely methods or ways of learning, planning for the teaching and learning process and media or learning facilities. The suggestions that can be put forward are the need for creativity of teachers to create interesting learning materials, for example using animation; and implementing interactive activities in the learning process, for example through games.